INOVASI MEDIA PEMBELAJARAN EDUKATIF DAN INTERAKTIF DALAM PENINGKATAN PEMAHAMAN KESEHATAN REPRODUKTIF PADA MASA REMAJA - Nuruniyah Nuruniyah; Ayu Rizky; Nita Putriasti Mayarestya; Siti Masdah; Lidia Hastuti (Universitas Mataram, 2025)
Puberty is an important phase in adolescent development characterized by changes in the physical, emotional, and functional of the reproductive organs. However, the limited knowledge of students about reproductive health is still a problem, mainly due to traditional learning methods that are less interesting and interactive. This research aims to improve students' understanding of reproductive health through innovative educational and interactive learning media at SMP Muhammadiyah 2 Pontianak. Method the used is community service with a participatory approach through observation, interviews, as well as pre-tests and post-tests for students in grades VII and VIII. The material is delivered using interactive media such as educational videos, games, and open discussions to create a fun learning atmosphere and facilitate students in understanding sensitive material without embarrassment. Results The showed a significant improvement in student understanding, with the change in the category from